Pengaruh Kebijakan Dividen, Keputusan Investasi dan Keputusan Pendanaan Terhadap Nilai Perusahaan pada Sektor Basic Materials di BEI 2020-2023 - Rajagukguk, Helvi Febriana; Gultom, Robinhot; Purba, Dimita Hemalli Premasari (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This research aims to determine how Dividend Policy, Investment Decisions, and Financing Decisions influence Firm Value in Basic Materials sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. The variables used in this study are independent variables (X) consisting of dividend policy proxied by the Dividend Payout Ratio, investment decisions proxied by the Price Earning Ratio, financing decisions proxied by the Debt to Equity Ratio, and the dependent variable (Y) is Firm Value proxied by Tobin’s Q. The sample in this study was obtained using purposive sampling method. Based on the established criteria and data processing method, 19 companies were determined to be the research sample. The data analysis technique used is multiple linear regression. The results of this study indicate that partially, dividend policy has a negative and significant effect on firm value, investment decisions have a positive and significant effect on firm value, and financing decisions do not have a significant effect on firm value. Simultaneously, the variables of Dividend Policy, Investment Decisions, and Financing Decisions significantly affect Firm Value.